Establishment of a Rat Model of Alzheimer's Disease by Introducing Human Triple Mutant APP Gene into Hippocampus via Brain Stereotactic Technology - XIAO Linlin; YANG Yixuan; LI Shanshan; LUO Lanshiyu; YIN Siwei; SUN Juming; SHI Wei; OUYANG Yiqiang; LI Xiyi (Shiyan dongwu yu bijiao yixue)
Objective To establish a rat model of Alzheimer's disease (AD) expressing human triple mutant amyloid precursor protein (APP) in the hippocampus, and to provide a model for the study of disease mechanisms and drug development. Methods Twenty-four 12-week-old SPF-grade female SD rats were randomly divided into a blank control group, a virus control group and an experimental group, with eight rats in each group; among them, the experimental group received a stereotaxic injection of adeno-associated virus (AAV) carrying the human triple mutant APP and NanoLuc luciferase genes into the hippocampus. In vivo imaging was used to observe viral expression in the brains of rats in each group, the novel object recognition test was used to assess the recognition memory of the rats in each group, real-time fluorescent quantitative PCR was used to detect the expression level of the APP gene, HE staining was used to examine the brain histopathology, Nissl staining was used to assess the hippocampal lesions, and immunohistochemistry was used to detect the deposition of amyloid β-protein (Aβ). Results In vivo imaging showed that reporter fluorescence was detected in the brains of rats in both experimental and virus control groups. Fluorescence quantitative PCR showed that the expression level of the APP gene was significantly increased in the brains of rats in the experimental group (P<0.01). Novel object recognition test revealed that the recognition memory of rats in the experimental group was significantly reduced compared with that of the blank control group (P<0.01). Six months after recombinant AAV virus infection, HE staining and Nissl staining of brain tissues showed that the number of neurons and Nissl bodies in the CA1 region of the hippocampus in the experimental group was reduced and disorganized; immuno-histochemistry testing of the CA1 region of the hippocampus and the pyramidal cell layer of the experimental group revealed prominent brown deposits, indicating Aβ protein deposition. Conclusion The rat model successfully established by stereotaxic injection and AAV-mediated delivery of human triple mutant APP gene exhibits typical AD features, providing a valuable animal model for studying AD pathology and developing drug therapies targeting Aβ protein deposition.